Meso-scale three-dimensional modeling of bond in FRP-strengthened masonry - Ghiassi, Bahman (2012)
Performance of masonry elements externally strengthened with fiber reinforced polymers (FRPs) is intrinsically dependent on the bond behavior between the composite material and masonry substrate. Therefore, a sound understanding of the interface behavior is crucial at the design stage. In this paper, a three-dimensional model based on the smeared crack modeling approach is presented for investigating the bond behavior in FRP-strengthened masonry elements. The threedimensional aspects of bond behavior in FRP- strengthened masonry elements are investigated. Moreover, the effect of mortar joints in the bond behavior of strengthened masonry prisms is studied